Characterisation of peripheral and central components of the rat monoiodoacetate model of Osteoarthritis. Issue 4 (April 2019) - Lockwood, S.M.; Lopes, D.M.; McMahon, S.B.; Dickenson, A.H.
Summary: Objective: Pain is the main reason patients report Osteoarthritis (OA), yet current analgesics remain relatively ineffective. This study investigated both peripheral and central mechanisms that lead to the development of OA associated chronic pain. Design: The monoiodoacetate (MIA) model of OA was investigated at early (2–6 days post injection) and late (>14 days post injection) time points. Pain-like behaviour and knee histology were assessed to understand the extent of pain due to cartilage degradation. Electrophysiological single-unit recordings were taken from spinal wide dynamic range (WDR) neurons to investigate Diffuse Noxious Inhibitory Controls (DNIC) as a marker of potential changes in descending controls. Immunohistochemistry was performed on dorsal root ganglion (DRG) neurons to assess any MIA induced neuronal damage. Furthermore, qPCR was used to measure levels of glia cells and cytokines in the dorsal horn. Results: Both MIA groups develop pain-like behaviour but only late phase (LP) animals display extensive cartilage degradation. Early phase animals have a normally functioning DNIC system but there is a loss of DNIC in LP animals. We found no evidence for neuronal damage caused by MIA in either group, yet an increase in IL-1β mRNA in the dorsal horn of LP animals. Conclusion: The loss of DNIC in LP MIA animals suggests an imbalance in inhibitory and facilitatory descending controls, and a rise in the mRNA expression of IL-1β mRNA suggest the development of central sensitisation. Therefore, the pain associated with OA in LP animals may not be attributed to purely peripheral mechanisms.